The Influence of Digital Marketing and Brand Image with Fear of Missing Out (FoMO) as Mediation Variables on Decisions Purchase of Adidas Evo SL Products - Rahmawan, Muhammad Fahmi Shifta; Lutfiana, Ifa Dwi; Nasir, Jamal Abdul Nasir (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study aims to analyze the role of Fear of Missing Out (FoMO) as a mediating variable linking digital marketing and brand image to purchase decisions. The objective is to understand how external marketing stimuli and internal psychological factors jointly shape consumer decision-making behavior. Background Problems: The study addresses the question of whether digital marketing and brand image directly influence purchase decisions, and to what extent FoMO mediates these relationships in the context of running community members. Research Methods: A quantitative approach was applied, using a sample of 180 respondents drawn from a running community associated with the product. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS. Findings/Results: The findings show that digital marketing and brand image do not have a significant direct effect on purchase decisions. FoMO, as an internal psychological factor, has a positive and significant direct effect and fully mediates the relationship between both external variables and purchase decisions. Conclusion: The study concludes that FoMO functions as a full mediator, highlighting the dominant role of psychological drivers over external marketing stimuli in influencing purchase decisions.